The rest of us [videorecording (DVD)] - Francis, Alanna; Graham, Heather, 1970-; Nélisse, Sophie; Balfour, Jodi, 1987- (Gravitas Ventures, 2020)
Two mother-daughter duos must contend with their grief and complicated feelings for each other when the person who ties them together dies.